2006
DOI: 10.1074/jbc.m600034200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Functionally Relevant Residues of the Rat Ileal Apical Sodium-dependent Bile Acid Cotransporter

Abstract: The mechanisms underlying the transport of bile acids by apical sodium-dependent bile acid transporter (Asbt) are not well defined. To further identify the functionally relevant residues, thirteen conserved negatively (Asp and Glu) and positively (Lys and Arg) charged residues plus Cys-270 of rat Asbt were replaced with Ala or Gln by site-directed mutagenesis. Seven of the fourteen residues of rat Asbt were identified as functionally important by taurocholate transport studies, substrate inhibition assays, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 27 publications
3
26
0
Order By: Relevance
“…Note that substrate binding and translocation does not require fulfillment of all five features simultaneously. As mapped to the protein, our studies have putatively identified residues satisfying the first two features (21,(23)(24)(25); studies with ASBT orthologs and paralogs corroborate these assignments (26,27,37). However, there has been minimal progress toward identification of apolar residues involved in hydrophobic substrate-protein interactions.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Note that substrate binding and translocation does not require fulfillment of all five features simultaneously. As mapped to the protein, our studies have putatively identified residues satisfying the first two features (21,(23)(24)(25); studies with ASBT orthologs and paralogs corroborate these assignments (26,27,37). However, there has been minimal progress toward identification of apolar residues involved in hydrophobic substrate-protein interactions.…”
Section: Discussionmentioning
confidence: 76%
“…Here, we focused on the highly conserved, large extracellular loop 1 (EL1) spanning 27 amino acids (Val-99 -Ser-126) based on the following rationale. (i) The functional importance of charged protein residues during Na ϩ and bile acid binding events, as demonstrated by our group (21,25) and others (26), suggests functional involvement of Asp-120, Asp-122, and Asp-124, which are clustered along the distal half of EL1 during Na ϩ binding events. Moreover, numerous polar residues, also capable of long range electrostatic interactions with charged substrates, are present throughout the EL1 segment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The multidrug transporter ABCB1, for example, is functional after all the Cys residues are replaced with Ala; thus, Cys-less ABCB1 can be used as a scaffold in Cys-insertion scanning analysis, 27,28) but some Cys residues are essential for the function and correct intracellular localization of both ileal and hepatic SBATs. 1,9,10,12,13,29,30) In addition to considerable similarity between SLC10A1 and SLC10A2 in amino acid sequences (alignment of known mammalian SBATs results in 30% identity and 65% similarity), they share structural similarities, particularly in their hydrophobicity profiles, indicating that their membrane topology is similar. Nevertheless, the distribution of functional regions within the polypeptide chain has been suggested to be different between SLC10A1 and SLC10A2.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] These transporters and their homologous transporters do not share structural similarities with other Na þ -dependent secondary transporters. Even though analysis of naturally occurring and artificially induced mutations has identified some residues critical for the function of these transporters, [8][9][10][11][12][13][14][15][16][17][18][19][20][21] the strict localization of functionally important regions, such as substrate binding sites, has not been decided yet, and the secondary structure of SLC10A1 and SLC10A2 is still controversial. Cys insertion scanning and chemical modification using thiol modifiers are useful methods to determine functionally important regions and the topology of membrane transporters.…”
mentioning
confidence: 99%